Populasi Bakteri Penambat N2 Atmosfer pada Tanah Sawah yang Diberikan Herbisida dengan Berbagai Kandungan Bahan Aktif - Hendra Setiawan; Abdul Hadi; Fakhrur Razie (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Supporting the increase in agricultural production today cannot be separated from the use of herbicides in land preparation activities. Most of the herbicides applied to plants will eventually fall to the ground, then undergo changes and in a certain time will be absorbed by the clay fraction and organic matter in the soil, which is generally known as herbicide residue. Toxic herbicide residues in the soil can kill soil microbes, which are not actually the target (non-target microorganisms) so that they interfere with the activity of soil microorganisms which in turn can affect the nutrient cycle in the soil.This research was conducted with the aim of knowing the effect of giving herbicides with various types of active ingredients in paddy fields on the viability of N-fixing bacteria and their relationship to soil chemical properties.The research and analysis was carried out from November 2021 to January 2022. The method used in this study was the Completely Randomized Design (CRD) environmental design method with a single factor treatment design, namely the type of herbicide active ingredient. Based on the results of research that has been carried out, it is known that the herbicide Glyphosate can increase the population of atmospheric N2-fixing bacteria in the soil, while the herbicide Paraquat and Methyl Metsulfuron can suppress the population growth of atmospheric N2-fixing bacteria